2018 Global Internet of Things Summit (GIoTS) 2018
DOI: 10.1109/giots.2018.8534541
|View full text |Cite
|
Sign up to set email alerts
|

SWAMP: an IoT-based Smart Water Management Platform for Precision Irrigation in Agriculture

Abstract: Irrigation for agriculture is the biggest consumer of freshwater in the world, which makes a case for the intensive use of technology to optimize the use of water, reduce the consumption of energy and improve the quality of crops. While the Internet of Things (IoT) and other associated technologies are the natural choice for smart water management applications, their appropriateness is still to be proven in real settings with the deployment of on-site pilots. Also, IoT-based application development platforms s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 10 publications
0
38
0
2
Order By: Relevance
“…In terms of real water management, and not only turning the irrigation off when the soil is still moist, not many works were found. The SWAMP project, by C. Kamienski [17][18][19], was the main research found. The project consists of a full system, from software to hardware, that includes the use of sensors, drones and weather stations to retrieve data, LoRa and MQTT (Message Queuing Telemetry Transport) to transmit data and a set of models to adapt these values to create the best irrigation process for precision agriculture.…”
Section: Related Workmentioning
confidence: 99%
“…In terms of real water management, and not only turning the irrigation off when the soil is still moist, not many works were found. The SWAMP project, by C. Kamienski [17][18][19], was the main research found. The project consists of a full system, from software to hardware, that includes the use of sensors, drones and weather stations to retrieve data, LoRa and MQTT (Message Queuing Telemetry Transport) to transmit data and a set of models to adapt these values to create the best irrigation process for precision agriculture.…”
Section: Related Workmentioning
confidence: 99%
“…The work carried out by Myers et al [12] presents the improvement of intelligent water management and information technique to build active decision while releasing the water for the fruit trees and grasses. This study demonstrates the SWAMP-project using IoT based water conservation method for the correctness irrigation into the agriculture by Kamienski et al [13]. This study focuses on monitoring and managing the water resources using IoT based technique by Xiaocong et al [14].…”
Section: Review Of Literaturementioning
confidence: 99%
“…In EXEHDA-SF the Irrigation Decision Algorithm is based on the moment of irrigation defined by the user and considers the rain data and its intensity, both from the previous 12 hours and from the following 12 hours. Based on the average values in the literature [13], the decision to irrigate at EXEHDA-SF will be considered as a 25mm rainfall reference and as a 60% PoP.…”
Section: Algorithm For Irrigation Decisionmentioning
confidence: 99%